Das Kind mit APD und CAPD: Untersuchung zentraler auditiver Verarbeitungsstörungen und der Wirksamkeit des Hörtrainings - Agnieszka Kuniczuk (Linguistische Treffen in Wrocław)
In recent times, there has been a notable rise in the number of children exhibiting indications of Central Auditory Processing Disorders (CAPD). It is frequently the case that the symptoms exhibited by young people are overlooked, and the symptoms of the disorder are erroneously attributed to stupor, discourteous behaviour, reluctance to heed the instructions of adults and even hearing loss. This has significant implications for children’s communication and functioning in educational settings. The objective of this article is to highlight the existing issue, identify the fundamental symptoms of CAPD in accordance with the current state of research, and examine the possibilities of assessing the functioning of a child with Central Auditory Processing Disorders. Furthermore, potential avenues for examination and therapy for individuals with CAPD will be delineated. The article presents the case of a girl who exhibits such difficulties. Furthermore, it outlines the potential avenues for evaluating the client’s condition and suggesting tailored training programmes. The case of a child with Autism Spectrum Disorder (ASD) and Central Auditory Processing Disorder (CAPD) was selected for analysis. The article has both a theoretical and a practical dimension. The child’s condition was evaluated using an interview sheet, tests examining Central Auditory Processing Disorders, and methods and techniques aimed at neural networks to enhance brain neuroplasticity and improve Central Auditory Processing Disorders. The results of the Central Auditory Processing Disorder (CAPD) test and the effects of training were discussed. The proposals included in the article for both testing and auditory training of a child showing symptoms of CAPD are based on the author’s observations of both testing and therapy on a daily basis.